1996
DOI: 10.1016/s0092-8674(00)81309-4
|View full text |Cite
|
Sign up to set email alerts
|

p53 Protein Exhibits 3′-to-5′ Exonuclease Activity

Abstract: Highly purified p53 protein from different sources was able to degrade DNA with a 3'-to-5' polarity, yielding deoxynucleoside monophosphates as reaction products. This exonuclease activity was dependent on Mg2+ and inhibited by addition of 5 mM nucleoside monophosphates. This exonuclease activity is intrinsic to the wild-type p53 protein: it copurified with p53 during p53 preparation; only purified wild-type p53, but not identically purified mutant p53 proteins displayed exonuclease activity; the exonuclease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
191
0
3

Year Published

1997
1997
1999
1999

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 242 publications
(203 citation statements)
references
References 70 publications
9
191
0
3
Order By: Relevance
“…Although most of the experiments reported here were performed with such a p53 preparation, p53 protein puri®ed to homogeneity by immunoa nity procedures was used to verify the major conclusions made in this manuscript. Protein A-Sepharose columns cross-linked with p53-speci®c monoclonal antibody PAb421 were used to purify p53 protein from the extracts of infected cell as described (Mummenbrauer et al, 1996;Zhao et al, 1996).…”
Section: Overexpression and Isolation Of The Recombinant Murine Wt P53mentioning
confidence: 99%
“…Although most of the experiments reported here were performed with such a p53 preparation, p53 protein puri®ed to homogeneity by immunoa nity procedures was used to verify the major conclusions made in this manuscript. Protein A-Sepharose columns cross-linked with p53-speci®c monoclonal antibody PAb421 were used to purify p53 protein from the extracts of infected cell as described (Mummenbrauer et al, 1996;Zhao et al, 1996).…”
Section: Overexpression and Isolation Of The Recombinant Murine Wt P53mentioning
confidence: 99%
“…Therefore we suggest that p53, in addition to damage recognition, could be directly involved in DNA repair processes by several biochemical activities, namely by its non-sequencespeci®c DNA binding activity, its DNA reannealing activity, its ability to promote DNA strand transfer, and its 3'-45' exonuclease activity. Especially the p53 intrinsic 3'-45' exonuclease activity, localized within the p53 core domain (Mummenbrauer et al, 1996); could be an important player in repair activities of p53. Exonucleases are required for DNA replication, DNA repair and recombination and often enhance the ®delity of these processes.…”
Section: Biochemical Activities Of P53 Related To Dna Repairmentioning
confidence: 99%
“…Exonucleases are required for DNA replication, DNA repair and recombination and often enhance the ®delity of these processes. As mutant p53 is exonuclease de®cient (Mummenbrauer et al, 1996), and cells expressing a mutant p53 are defective in global NER Hanawalt, 1995, 1997;Wang and Prives, 1995;Mirzayans et al, 1996), this correlation might point to a possible role of the p53 exonuclease activity in DNA repair. The various biochemical activities of p53 and its interactions with viral and cellular proteins are summarized and related to p53 structure in Figure 1.…”
Section: Biochemical Activities Of P53 Related To Dna Repairmentioning
confidence: 99%
“…DNA damage caused by certain exogenous mutagens including epipodophyllotoxins induces wild-type p53, a transcription factor that recognizes DNA damage, blocks cell cycle progression in late Gl, and mediates either apoptosis or DNA repair (Clarke et al, 1993;Kastan et al, 1991;Kuerbitz et al, 1992;Lowe et al, 1993;Maltzman and Czyzyk, 1984). In addition, wildtype p53 has putative intrinsic 3'?5' exonuclease, DNA strand transferase and DNA strand annealing activities, which would be important in DNA repair (Bakalkin et al, 1994;Mummenbrauer et al, 1996;Oberosler et al, 1993). We previously showed that p53 was wild-type in 14 of 14 treatment-related leukemias with MLL gene translocations (Felix et al, 1996).…”
mentioning
confidence: 99%
“…In particular, the requisite exonucleolytic processing of 3' DNA free ends left by DNA topoisomerase II and nucleotide insertion invoke DNA repair in the translocation mechanism. Wild-type p53 is central to DNA repair and has proven indirect and putative intrinsic DNA repair activities that could be of relevance in joining MLL with its translocation partners (Bakalkin et al, 1994;Lowe et al, 1993;Mummenbrauer et al, 1996;Oberosler et al, 1993).…”
mentioning
confidence: 99%